Bioluminescent Zebrafish Transplantation Model for Drug Discovery - Hason, Martina; Jovicic, Jovana; Vonkova, Ivana; Bojic, Milan; Simon-Vermot, Theresa; White, Richard M.; Bartunek, Petr (Frontiers in Pharmacology, 2022)
In the last decade, zebrafish have accompanied the mouse as a robust animal model for cancer research. The possibility of screening small-molecule inhibitors in a large number of zebrafish embryos makes this model particularly valuable. However, the dynamic visualization of fluorescently labeled tumor cells needs to be complemented by a more sensitive, easy, and rapid mode for evaluating tumor growth in vivo to enable high-throughput screening of clinically relevant drugs. In this study we proposed and validated a pre-clinical screening model for drug discovery by utilizing bioluminescence as our readout for the determination of transplanted cancer cell growth and inhibition in zebrafish embryos. For this purpose, we used NanoLuc luciferase, which ensured rapid cancer cell growth quantification in vivo with high sensitivity and low background when compared to conventional fluorescence measurements. This allowed us large-scale evaluation of in vivo drug responses of 180 kinase inhibitors in zebrafish. Our bioluminescent screening platform could facilitate identification of new small-molecules for targeted cancer therapy as well as for drug repurposing.